2015
DOI: 10.5751/ace-00751-100202
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in resident bird communities associated with cloud forest patch size in Central Veracruz, Mexico

Abstract: ABSTRACT. Avian communities in cloud forests have high levels of endemism and are at major risk given the accelerated rate of habitat fragmentation. Nevertheless, the response of these communities to changes in fragment size remains poorly understood. We evaluated species richness, bird community density, community composition, and dominance as indicators of the response to fragment size in a fragmented cloud forest landscape in central Veracruz, Mexico. Medium-sized fragments had statistically higher than exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…Here, we have demonstrated the importance of strictly protected areas for globally declining species. Our results were mirrored elsewhere in Mexico, in both the Lacandona rain forest of Chiapas and the cloud forest of Veracruz, where larger, undisturbed stretches of forest were valuable for specialists (Carrara et al, 2015) and threatened (Rueda-Hernandez et al, 2015) bird species, whereas habitat generalists benefited from more fragmented landscapes. S4).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Here, we have demonstrated the importance of strictly protected areas for globally declining species. Our results were mirrored elsewhere in Mexico, in both the Lacandona rain forest of Chiapas and the cloud forest of Veracruz, where larger, undisturbed stretches of forest were valuable for specialists (Carrara et al, 2015) and threatened (Rueda-Hernandez et al, 2015) bird species, whereas habitat generalists benefited from more fragmented landscapes. S4).…”
Section: Discussionsupporting
confidence: 73%
“…In addition to those observed in this study (see Table S3), the SGBR's strictly protected areas are also the only parts of the reserve where vulnerable (IUCN Red List) and highly sensitive (particularly to hunting) species such as Great Curassows Crax rubra, Bearded Wood-partridges Dendrortyx barbatus and Military Macaws Ara militaris nest. Our results were mirrored elsewhere in Mexico, in both the Lacandona rain forest of Chiapas and the cloud forest of Veracruz, where larger, undisturbed stretches of forest were valuable for specialists (Carrara et al, 2015) and threatened (Rueda-Hernandez et al, 2015) bird species, whereas habitat generalists benefited from more fragmented landscapes.…”
Section: Discussionsupporting
confidence: 73%
“…Although fragmentation is well-known for reducing gene flow, it has far-reaching consequences at all ecological levels, including ecosystem services. In general, fragmentation has a negative impact on communities; resulting in a decline in species richness (e.g., Borgella et al, 2001;Kumar and O'Donnell, 2007;Hundera et al, 2013;Mohandass et al, 2014;Rovero et al, 2014), and changes in species composition in response to fragmentation has also been consistently reported (e.g., Larrea and Werner, 2010;Mohandass et al, 2014;Rueda-Hernandez et al, 2015;García-Martínez et al, 2017;Herrera-Paniagua et al, 2017). However, some studies have highlighted that certain spatial characteristics such as fragment area and isolation have no effect on abundance, density or diversity (Muriel and Kattan, 2009;Ulrich et al, 2016).…”
Section: Research Priorities For Habitat Degradation In Tmfmentioning
confidence: 99%
“…While the extent of degradation may lead to conflicting results, deeper examination of species functional traits, which are indicators of habitat use, reveal that some groups within a community are more affected than others. For instance, two avian studies independently concluded that understory insectivores and canopy frugivores were more sensitive to fragmentation than other functional groups (Kattan et al, 1994;Rueda-Hernandez et al, 2015). Thus, within-community differences should be accounted for in future fragmentation research in TMF.…”
Section: Research Priorities For Habitat Degradation In Tmfmentioning
confidence: 99%
See 1 more Smart Citation